2014
DOI: 10.4236/ojn.2014.48061
|View full text |Cite
|
Sign up to set email alerts
|

An Audit of Admissions to Intensive Care Unit at Kamuzu Central Hospital in Malawi

Abstract: Results are presented of a retrospective audit of admissions to the Intensive Care Unit (ICU) of Kamuzu Central Hospital in Lilongwe, Malawi, which is a tertiary referral facility. The audit was conducted for a period of one year spanning from January to December, 2012. The objectives of the audit were to: describe the profile of admissions and treatment outcomes of the admissions and identify main causes of mortality in ICU of the facility. The admission book and patients' records were reviewed retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…The high mortality noted in our patients with significant intracranial trauma is often a combination of several factors such as the severity of the injury, delayed emergency medical services, lack of proper helmets, limited use of seatbelts and lack of appropriate resources. Interestingly, similar findings have been noted in other resource-constrained developing countries in: Africa, Asia, Middle East, and Central and South America (8)(9)(10)(11)(12)(13)(14)(15)(16). Also, like in these other ICUs, the preponderance of male patients (57.6%) in our ICU is attributable to the higher male involvement in trauma especially motor vehicle crashes and interpersonal violence.…”
Section: Discussionsupporting
confidence: 87%
“…The high mortality noted in our patients with significant intracranial trauma is often a combination of several factors such as the severity of the injury, delayed emergency medical services, lack of proper helmets, limited use of seatbelts and lack of appropriate resources. Interestingly, similar findings have been noted in other resource-constrained developing countries in: Africa, Asia, Middle East, and Central and South America (8)(9)(10)(11)(12)(13)(14)(15)(16). Also, like in these other ICUs, the preponderance of male patients (57.6%) in our ICU is attributable to the higher male involvement in trauma especially motor vehicle crashes and interpersonal violence.…”
Section: Discussionsupporting
confidence: 87%
“…The outcome of our patients with mortality of around 33.82% seems a bit high in comparison to ICUs in developed countries but in regard to developing countries, it seems to be similar to other developing countries. 7,8,9 This may be due to critical condition of patients admitted to our center where very sick patients are referred from all across the country.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, study by Gundo et al maximum number of patients who expired were below 40years of age. 11 In some studies no association was observed between age and mortality. 3,10 The most common source of patients to ICU was from emergency (48.5%) and least number of transfer in was from operation theatre.…”
Section: Discussionmentioning
confidence: 99%